Markell and Voge's medical parasitology - Markell, Edward K.; John, David T.; Krotoski, Wojciech A. (Singapore : Elsevier (Singapore) Pte. Ltd., 1999)
The text explores arthropods both as parasites in their own right and as vectors or intermediate hosts for other parasites so students can understand the direct and indirect impact that they have on health. Advances in this field are reflected in the modifications of this text. New life cycle drawings are included. Halftone illustrations with color plates. Previous edition was entitled: Medical Parasitology, c1992
Introduction -- Parasites, parasitism, and host relations -- Lumen-dwelling protozoa -- Malaria -- Other blood-and tissue-dwelling protozoa, color plates -- The trematodes -- The cestodes -- The intestinal nematodes -- The blood-and-tissue-dwelling nematodes -- Arthropods and human disease -- Parasitic infections in immunocompromised hosts -- Signs and symptoms of parasitic disease -- Pseudoparasites and pitfalls -- Examination of stool specimens -- Examination of blood, other body fluids and tissues, sputum, and urine -- Immunodiagnostic techniques -- Index.
Includes index.
Keywords: PARASITES